2019
DOI: 10.1002/ijc.31776
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of colon and rectum cancer incidence across 612 SEER counties, 2000–2014

Abstract: Recent analyses have suggested decreases over time in colorectal cancer incidence at older ages (≥55 years) but increases at younger ages (20-54 years). Understanding the geographic heterogeneity of incidence facilitates resource allocation for potential interventions and advances our knowledge of differential etiologies for these cancers. We performed age-period-cohort analysis using 2000-2014 county-level incidence from the Surveillance, Epidemiology, and End Results (SEER) database, estimating relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Countries that have implemented prevention programs have shown a reduction in CRC incidence [13][14][15]. For example, CRC death rates in the U.S. have declined 53% from 1970 to 2016, largely because of screening and improvements in treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Countries that have implemented prevention programs have shown a reduction in CRC incidence [13][14][15]. For example, CRC death rates in the U.S. have declined 53% from 1970 to 2016, largely because of screening and improvements in treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies (11%) reported the incidence rate with no further specification. Two of these studies described the incidence as mainly the frequency of new cases [ 77 , 150 ], four obtained incidence rates via linear modelling [ 32 , 41 , 48 , 159 ], and two defined incidence as the percentage of CRC cases among different age groups [ 119 , 120 ]. Additional details are provided in Additional files 1 , 3 : Table 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…In each of these analyses, we included data from all 17 SEER registries. We used the novel Bayesian hierarchical APC models described in Chernyavskiy et al ( 7 , 8 ). These models extend traditional APC models ( 13-15 ) by including registry-specific random intercepts to allow mean incidence rates, compared with the SEER average, to vary between registries.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we use novel multi-level age-period-cohort (APC) models ( 7 , 8 ) to determine how incidence patterns of ER-negative breast cancer among NHW, NHB, and HW women vary across different regions of the United States, represented by 17 SEER registries. Our models allow us to produce stable estimates of mean rates and age-adjusted trends (so-called net drifts) for each combination of registry, race or ethnic group, and age group, taking into account the limited numbers of women in some strata.…”
mentioning
confidence: 99%